2018
DOI: 10.1021/acs.langmuir.8b02449
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Organic Functionalization of SiO2 with Propanoyl Chloride

Abstract: The reaction mechanism of propanoyl chloride (C 2 H 5 COCl) with −SiOH-terminated SiO 2 films was studied using in situ surface infrared spectroscopy. We show that this surface functionalization reaction is temperature dependent. At 230 °C, C 2 H 5 COCl reacts with isolated surface −SiOH groups to form the expected ester linkage. Surprisingly, as the temperature is lowered to 70 °C, the ketone groups are transformed into the enol tautomer, but if the temperature is increased back to the starting exposure tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 80 publications
3
18
0
Order By: Relevance
“…As shown in Figure 3a, upon the exposure of a −SiOH-terminated SiO 2 surface to CAZ, a sharp decrease in absorbance is observed at ∼3750 cm −1 , which indicates the reaction of CAZ with the isolated −SiOH species on the surface. 8,41,53 Further, as observed in previous work, it also confirms that the isolated −SiOH species are the primary reactive sites on the plasma-deposited SiO 2 surface. 8 The low wavenumber tail indicates the reaction of CAZ with surface vicinal (weakly hydrogen bonded) -SiOH groups as well (see Figure S1).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As shown in Figure 3a, upon the exposure of a −SiOH-terminated SiO 2 surface to CAZ, a sharp decrease in absorbance is observed at ∼3750 cm −1 , which indicates the reaction of CAZ with the isolated −SiOH species on the surface. 8,41,53 Further, as observed in previous work, it also confirms that the isolated −SiOH species are the primary reactive sites on the plasma-deposited SiO 2 surface. 8 The low wavenumber tail indicates the reaction of CAZ with surface vicinal (weakly hydrogen bonded) -SiOH groups as well (see Figure S1).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…We have previously shown that the ∼3650 cm −1 mode corresponds to the −SiOH groups that are embedded in the bulk, while the isolated −SiOH groups are the surface reactive sites. 8 Figure 2b shows the infrared absorbance spectrum of a typical plasma-deposited SiN x film on a bare ZnSe IRC. The reference spectrum was recorded immediately prior to the plasma strike; therefore, the spectrum contains contributions from both the bulk and surface vibrational modes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiN x films were grown via ALD in the surface analysis chamber depicted in Figure a, which has been described in detail previously . Briefly, this chamber is equipped with an inductively coupled plasma source operated at 13.56 MHz, and an ATR‐FTIR spectroscopy setup that allows for the detection of surface species.…”
Section: Methodsmentioning
confidence: 99%
“…The SiN x films were grown via ALD in the surface analysis chamber depicted in Figure 1a, which has been described in detail previously. [21][22][23] Briefly, this chamber is equipped with an inductively coupled plasma source operated at 13.56 MHz, and an ATR-FTIR spectroscopy setup that allows for the detection of surface species. We used 1 × 10 × 50 mm trapezoidal ZnSe internal reflection crystals (IRCs) as substrates, which provide submonolayer sensitivity to surface adsorbates due to the~25 internal reflections on each face.…”
Section: Methodsmentioning
confidence: 99%